PENGARUH STRATEGI PEMBELAJARAN GENERATIF TERHADAP KEMAMPUAN KOMUNIKASI SISWA KELAS VII SMP NEGERI 2 TANJUNG EMAS KABUPATEN TANAH DATAR - Aima, Zulfitri (Universitas Ahmad Dahlan, 2012)
The cause of lakness of communication ability in mathematic learning at SMPN 2 Tanjung Emas is due to the teacher centered of teaching method applied in the school One of the best ways to solve this problem is by applying Generative Learning Strategy. The purpose of this research is to know whether communication ability of students taught with generative of learning strategy better than those taugh with common learning strategy. The research was conduc ted at VII class of SMPN 2 Tanjung Emas 2009/2010 academic year. This research used quasi experiment method with posttest Control Group Desigh. Experimental group used generative learning strategy and a control group used conventional method. Data were collected through achievement tests. The analysis showed that students communication ability of students taught with generative of learning strategy better than those taught with common learning strategy.